International Conference on Nanotechnology 2012 (ICONT 2012) : Program Book & Compilation of Abstracts - Saifful Kamaluddin, Muzakir; Izan Izwan, Misnon; Rajan, Jose; M. M., Yusoff (Universiti Malaysia Pahang, 2012)
ICONT 2012 is the third event in this series, and this year, Universiti Malaysia Pahang was given a previlages to organized the conference with collaboration of Pahang State Government, SIRIM Berhad, Academy of Sciences Malaysia, National Nanotechnology Directorate, Malaysia Nanotechnology Association, Ministry of Higher Education and Bruker (M) Sdn Bhd. The conference will have total of 148 papers comprising six plenary, two keynotes, eight invited 98 orals and 34 posters, with participation from 16 countries.